Knowledge and Culture-Based Development Policy Scenarios Using the PROMETHEE Method - Nizar, Nefo Indra (Universitas Negeri Semarang, 2024)
Knowledge and culture-based development is carried out by relying on knowledge and cultural resources as development capital. Development policy scenarios are needed to carry out development programs. Some of the development programs outlined in the national development plan are strengthening economic resilience for quality and equitable growth, reducing income inequality and alleviating poverty, as well as increasing competitiveness. The purpose of this study is to determine the priority scale based on economic development policy scenarios on the basis of knowledge and cultural resources in Indonesia. The research method is MCDA decision analysis (Multi-Criteria Decision Analysis) with the PROMETHEE method (Preference Ranking Organization Method for Enrichment Evaluation). PROMETHEE is a sequencing method based on a binary relationship between two or more alternatives. Meanwhile, to calculate the score of each program and development objectives, the primary component analysis technique is used. The data used is secondary data which is mostly sourced from the Central Bureau of Statistics. The results of the research show that the knowledge and culture-based development scenarios based on the sequence are as follows. First, strengthening economic resilience and increasing GRDP per capita. Second, increasing competitiveness, and third is reducing income inequality and the number of the poor.